SAT0502 Combined Clinical, Laboratory and Magnetic Resonance Imaging (MRI) Evaluation of Response to Anti-TNF Agents in Large Vessel Vasculitis (LVV). (23rd January 2014) - Horger, M.; Xenitidis, T.; Koetter, I.; Claussen, C. D.; Henes, J.
Abstract : Background: Treatment of LVV remains challenging. Patients usually respond to glucocorticosteroids (GC) therapy, but often relapse on tapering of the GC dose or after GC withdrawal. Anti-TNF agents represent an alternative in therapy refractory giant cell arteritis (GCA) and Takayasu arteritis (TA). In this study, we assessed the clinical, serologic, and radiographic outcomes of nine patients with LVV treated with anti-TNF agents. Objectives: Evaluation of the potential benefit of using magnetic resonance imaging (MRI) for response monitoring to anti-TNF agents in patients with large vessel vasculitis refractory to GC and cyclophosphamide (CYC) therapy. Methods: The correlation between ESR, CRP, clinical evaluation score (BVASnew) and MRI parameters was evaluated in 9 patients (9 female; mean age, 40.9) with TA (n=6) and GCA (n=3) both at baseline and follow up (FU). 3 patients received adalimumab and 6 had infliximab, 1 patient switched from infliximab to adalimumab and was counted twice. Mean therapy duration was 20.7 months (range, 3-72) whereas mean MRI follow up interval was 15.8 months (range, 3-48). Five patients have had steroid sparing medication with methotrexate or azathioprine before the switch to CYC. Results: At baseline mean ESR value was 16.2 (range, 5-38). ESR was increased only in 5 patients. Mean CRP value was 1.6 (range, 0.04-7.7). BVASnew was 2.1 (range, 2-5.5). Two patients presented a normal BVASnew. T2-signal intensity in the vessel wall was increased in 2 patients and normal in 7 patients. All patients exhibited increased vessel wall contrast-enhancement whereas the outer vessel wall edges were either ill-defined (n=4) or well-defined (n=5). Mean vessel wall thickness was 3.9 (range, 3-5.5). At follow up, mean ESR dropped to 12 (range, 5-32), CRP to 0.5 (range, 0.01-1.99) whereas BVASnew normalised in all patients). Only 1 patient had an increased ESR and 3 had a still increased CRP. 7 patients clinically benefited very well from the therapy, 2 patients showed progressive disease despite anti-TNF treatment, both were switched to tocilizumab. T2-signal intensity dropped in 1 patient (only 1 x increased and 8 normal); aortic wall contrast-enhancement normalized in 4 patients and stayed pathologically increased in 5 patients. Mean vessel wall thickness dropped to 2.7 (range, 2-5.5) whereas only 1 patient presented ill-defined outer vessel contours. There was no new stenosis or luminal occlusion at FU. From the 5 patients presenting still pathological aortic wall thickness and contrast-enhancement at 1 st FU only 1 revealed a pathological CRP value whereas ESR was in all in normal range. In 4 patients with persistent increased contrast-enhancement at 1stFU and 1 patient with normalization of all MRI parameters at 1 st FU, a 2 nd FU was performed (3 x MRI and 2 x 18F-FDG-PET/CT) which confirmed interim MRI-based results showing residual activity (n= 4) or inactivity (n=1). Conclusions: The course of clinical and serological biomarkers proved helpful for response evaluation in patients with large vessel vasculitis receiving experimental anti-TNF treatment. However, MRI surrogate biomarkers seemed to be more sensitive signalling more often the presence of residual (subclinical) activity of the autoimmune process. Disclosure of Interest: None Declared